Pola Pembiayaan Koperasi Syariah Dalam Meningkatkan Kesejahteraan Masyarakat Di Tanjung Balai - Humaidi Sitompul; Marliyah Marliyah (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
Cooperatives are one of the vessels used by a large part of society in the development of economic activity. In addition to economic activity, the foundations and principles in cooperatives are a reflection for Indonesians in the family system. The purpose of this study to determine whether such a cooperative can be said to participate in building the community economy in Tanjung Balai City should be studied and observed in more depth. As for this type of research, it is a descriptive qualitative research. This means that the researcher tries to provide a view and an overview while the researcher will directly plunge into the public through the process of field observation, in-depth interview (in-depth interview) as well as face-to-face and discussion. The data collection technique in this study uses observation, interview, and documentation techniques with researchers as key instruments that are always directly involved in all research processes.